The Influence of Physical Therapists’ Beliefs and Attitudes About Ageing on Expectations About Outcomes in a Hypothetical Patient - Gregory W. Hartley; Mateo Serrano; Kathryn E. Roach (Journal of Ageing and Longevity)
Background: The aim of this study was to analyze the influence of beliefs and attitudes of practicing physical therapists (PTs) about aging on their expectations concerning the behavior and outcomes of patients with orthopedic conditions. We hypothesized that some beliefs and attitudes would be related to expectations of worse outcomes in older patients compared to clinically identical younger patients. Methods: Seventy-one (71) practicing PTs with a mean age of 40 years (±10.44, range 24–67) were recruited via snowball sampling and asked to participate in a three-part online questionnaire. For part 1, participants were randomly assigned a hypothetical case involving either a 42-year-old or an 85-year-old patient s/p surgical repair of a femoral shaft fracture. Thirty-five (35) participants were randomly assigned to the young case group (YCG) and 37 to the old case group (OCG). Participants were asked questions related to their expectations concerning the patient’s clinical and functional potential, response and adherence to physical therapy, and patient responsibility for their own outcomes. For part 2, all participants completed the Kogan Attitude Toward Old People Scale consisting of 34 paired (positive/negative) statements. Part 3 consisted of subject demographics. Results: Participants in the YCG and the OCG were similar in age (41 vs. 40 years), PT experience (16.7 vs. 14.8 years), gender (82.9% vs. 86.5% female), and positive Kogan score (69.5 vs. 68.2). The groups differed in belief the patient would return to their prior level of function. YCG believed it was “extremely likely”, while the OCG believed it was “moderately likely”. In the OCG, greater likelihood that the patient would return to prior level of function was related to stronger belief that “Most ageing adults are really no different from anybody else” (r = 0.35). Conclusion: In general, physical therapist participants in this study agreed with positive attitudes and beliefs about aging adults as measured by total positive Kogan score. The only outcome expectation that appeared to be influenced by the age of hypothetical patient was return to prior level of function. Although some specific age-related beliefs were correlated to expectation of return to prior level of function, the positive Kogan score was not. It is possible that age related differences in expectations of return to prior level of function were influenced by clinical experience rehabilitating older patients rather than negative attitudes and beliefs about aging.